Estudo das propriedades luminescentes do CaYAl3O7 puro e dopado com íons terra raras produzido via método Pechini - Bispo, Giordano Frederico da Cunha (2017)
The CaYA3O7(CYAM) is an oxide belonging to the melilite family that shows luminescent properties when doped and/or codoped with rare earth ions. Several applications have been pointed out as temperature sensor, emergency light, sensing structural damage and solid-state light source for white LED’s. This material has been produced via state solid reaction, combustion synthesis (SHS) and sol-gel method. These methods have been shown some problems as high temperatures and huge time of calcination as well as presence of secondary phases. Pechini method was used in the present work to produce CYAM undoped and doped with rare earth ions aiming to solve these problems. The main aims are preparing the material via this method showing that it has advantages, as compared to previous methods, and to study the luminescence properties of CYAM. The optimum synthesis conditions were determined to be at 1000°C/4h. The synthesized particles are within the submicrometers size range with and irregular shape due to coalescence effect. The undoped CYAM presented luminescence emission in the blue region and this is the first time that this feature is reported. The emission spectra analysis pointed that at least six individual bands composed the intrinsic emission of CYAM and that peaks at 2,57, 2,94 and 3,23 eV were responsible for most of the emitted light. The excitation spectra and lifetime measurements analysis showed that the main emissions are due to F and F+ centres in the matrix. The self-trapping emission was found to be located at 4,40 eV with the exciton creation energy at 6,50 eV. The band gap energy was also determined and it was found to be 6,80 eV. The spectra of the doped CYAM samples showed that all rare earth ions prefer to substitute at Ca/Y site exhibiting spectra that are characteristic of low symmetry sites. Finally, the data obtained from the excitation and emission spectra of doped samples supplemented by the exciton and band gap energies allowed to build a diagram with energy position of all 4f n and 4f n-15d1 ground states for divalent and trivalent lanthanides. This model predicted with reasonable accuracy the 4f-5d1 transition for Tb3+ and Pr3+, besides charge transfer band for Sm3+. The energy diagram can be used to interpret various luminescence characteristics of CYAM.